2020
DOI: 10.1152/jn.00224.2020
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-cellular prion protein complex formation on astrocytes

Abstract: Traumatic brain injury (TBI) is one of the most common neurological disorders causing memory reduction, particularly short-term memory (STM). We showed that during TBI-induced inflammation, increased blood content of fibrinogen (Fg) enhanced vascular protein transcytosis and deposition of extravasated Fg in vasculo-astrocyte interfaces. In addition, we found that deposition of cellular prion protein (PrPC) was also increased in the vasculo-astrocyte endfeet interface. However, association of Fg and PrPC was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…The data showed that Fg was co-localized and thus strongly associated with astrocyte ICAM-1 and PrP C , suggesting that it is possibly binding to these receptors on the surface of astrocytes. This is the first time a Fg specific interaction with astrocytes was visualized, confirming our previous finding that Fg could be associated with ICAM-1 [ 21 ] and PrP C with high specificity [ 16 , 36 , 39 ]. Thus, the increased respective PLA signals can be the result of a Fg interaction with over-expressed astrocyte ICAM-1 and PrP C .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The data showed that Fg was co-localized and thus strongly associated with astrocyte ICAM-1 and PrP C , suggesting that it is possibly binding to these receptors on the surface of astrocytes. This is the first time a Fg specific interaction with astrocytes was visualized, confirming our previous finding that Fg could be associated with ICAM-1 [ 21 ] and PrP C with high specificity [ 16 , 36 , 39 ]. Thus, the increased respective PLA signals can be the result of a Fg interaction with over-expressed astrocyte ICAM-1 and PrP C .…”
Section: Discussionsupporting
confidence: 89%
“…Our observations of Fg-induced increases in astrocytic IL-6, CXCL-10 and CCL2 along with previously shown overexpression of tyrosine receptor kinase B [ 21 ] and PrP gene [ 16 ], suggest that Fg induces activation of astrocytes with functional polarization towards their neurotoxic, A1 phenotype [ 44 , 45 ], potentially exacerbating inflammatory conditions typically found during TBI [ 46 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Cellular prion protein (PrP C ) is a glycosylphosphatidylinositol-anchored glycoprotein abundantly expressed on the surfaces of neurons [ 13 ], while intercellular adhesion molecule-1 (ICAM-1) is a transmembrane glycoprotein that is constitutively expressed at low levels in unstimulated endothelial cells [ 14 ] and neurons [ 15 , 16 ]. Both PrP C [ 17 ] and ICAM-1 [ 18 , 19 ] are known Fg receptors. An increase in ICAM-1 expression was attributed to stimulation by inflammatory cytokines and oxidant species [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%